THE ROLE OF PSYCHOLOGICAL CAPITAL OF TEACHING STAFF TO IMPROVE FOREIGN LANGUAGE COURSE INSTITUTIONS IN PALU CITY - Awwab, Ashril; Natsir, Syahir; Fadjar, Adfiyani (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to analyze the role of Psychological capital in the self-development of teaching staff and the quality of foreign language courses in Palu City. This type of research is descriptive and qualitative, aimed at describing existing phenomena, both natural and human-made, which pay more attention to characteristics, quality, and interrelationships between activities. The informants in this research are teaching staff who have had work experience at the relevant course institution for approximately two years and play an active role in every teaching and learning process, totaling six people. This research uses the interactive model analysis method. The results of this study show that all dimensions of Psychological Capital among the teaching staff of the two English language course institutions can improve the quality of the teaching staff and enhance the quality of the two English language courses.